Analysis of Marta Christina Tiahahu Literacy Park as a New Tourism Object in Jakarta - Wardhani, Hilda Sari; Farrah, Farrah (Program Studi Hospitality dan Pariwisata, 2023)
This research discusses the readiness of Christina Martha Tiahahu's literacy park as a new tourist attraction in Jakarta. Public spaces in this capital city have an aesthetic architectural design, so they can be used as Instagramable photo spots and are expected to become new tourist attractions in urban areas. However, to become a tourist destination, the facilities that are owned still need to be studied to see whether this park is ready to become a new tourist object or needs additional equipment so that it is expected to increase the attractiveness of visitors. This research was designed with a descriptive method, namely research that leads to the disclosure of existing facts. Data collection was in the form of a literature review and direct observation to see the facilities and infrastructure owned by Blok M Literacy Park. Looking at its development and field facts the Martha Christina Tiahahu Literacy Park is currently not just a park, but its function as a tourist destination that has recreational functions, educational functions, the interaction function. As an indicator of tourism development, the level of facilities and infrastructure of the Martha Christina Tiahahu Literacy Park as a new tourist attraction has reached 80%, which includes, objects, access, accommodation, facilities, transportation, catering services, recreational activities, communication, shopping, security, cleanliness, religious facilities, and sports facilities. What is not yet available is the banking system and educational facilities. However, from this readiness, this Literacy Park is capable enough to become a new tourist destination for the community.